Anomalous lattice behavior of vanadium pentaoxide (V2O5): X-ray diffraction, inelastic neutron scattering and ab initio lattice dynamics12. Issue 27 (30th June 2017) - Singh, Baltej; Gupta, Mayanak Kumar; Mishra, Sanjay Kumar; Mittal, Ranjan; Sastry, P. U.; Rols, Stephane; Chaplot, Samrath Lal
Abstract : van der Waals and Hubbard interactions are found to play an important role in the structure and dynamics of α-V2 O5 . Abstract : We present structural and dynamical studies of layered vanadium pentaoxide (V2 O5 ). The temperature dependent X-ray diffraction measurements reveal highly anisotropic and anomalous thermal expansion from 12 K to 853 K. The results do not show any evidence of structural phase transition or decomposition of α-V2 O5, contrary to the previous transmission electron microscopy (TEM) and electron energy loss spectroscopy (EELS) experiments. The inelastic neutron scattering measurements performed up to 673 K corroborate the result of our X-ray diffraction measurements. The analysis of the experimental data is carried out using ab initio lattice dynamics calculations. The important role of van der Waals dispersion and Hubbard interactions in the structure and dynamics is revealed through ab initio calculations. The calculated anisotropic thermal expansion behavior agrees well with temperature dependent X-ray diffraction. The mechanism of anisotropic thermal expansion and anisotropic linear compressibility is discussed in terms of calculated anisotropy in the Grüneisen parameters and elastic coefficients. The calculated Gibbs free energy in various phases of V2 O5 is used to understand the high pressure and temperature phase diagram of the compound.